2013
DOI: 10.1016/j.rmed.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of rifabutin for rifabutin-susceptible, multidrug-resistant tuberculosis

Abstract: RFB is useful as an additional drug in the treatment of MDR-TB in patients with RFB-susceptible MDR-TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
(30 reference statements)
1
28
0
Order By: Relevance
“…These studies suggest that low-level RIF-resistance can be overcome by the use of higher RIF doses or alternatively, by replacing RIF with RFB [9], [10]. A retrospective study in South Korea showed an 85.7% (12/14) treatment success in patients with RFB-susceptible MDR-TB infections who received RFB as an additional drug [19]. In our study, the MIC distribution for RFB was above the ECOFF, but below the standard CC.…”
Section: Discussionmentioning
confidence: 45%
“…These studies suggest that low-level RIF-resistance can be overcome by the use of higher RIF doses or alternatively, by replacing RIF with RFB [9], [10]. A retrospective study in South Korea showed an 85.7% (12/14) treatment success in patients with RFB-susceptible MDR-TB infections who received RFB as an additional drug [19]. In our study, the MIC distribution for RFB was above the ECOFF, but below the standard CC.…”
Section: Discussionmentioning
confidence: 45%
“…Studies from low HIV settings have reported that 13–26% of MDR-TB isolates show sensitivity to RFB (Chen et al, 2012; Jo et al, 2013; Schon et al, 2013). However, there is limited information on the frequency of RFB susceptibility among MDR-TB isolates in an HIV endemic region.…”
Section: Introductionmentioning
confidence: 99%
“…Although this was a small retrospective study, the findings are encouraging given their support of the clinical relevance of differential RFB/RIF resistance. 31 More clinical trials are needed to confirm the effectiveness of RFB in RFB-susceptible RIF-resistant TB.…”
Section: Discussionmentioning
confidence: 99%